Chloroplast genome of Gaura parviflora Douglas and its comparative analysis - Bin Zhang; Ruige Wu; Meng Liu; Xiaoran Cai; Yueqin Cheng (Mitochondrial DNA. Part B. Resources, 2021)
Gaura parviflora Douglas (Onagraceae) is an annual or perennial herbaceous plant from the prairie of North America. It has become a harmful exotic invading plant in China due to its strong adaptability, fast growth, massive propagation and reproduction. The complete chloroplast (cp) genome of G. parviflora was reported in this study. The size of the complete cp genome of G. parviflora is 161,318 bp in length, including a pair of inverted repeat (IR) regions of 27,402 bp, a large single-copy (LSC) region of 89,132 bp, and a small single-copy (SSC) region of 17,382 bp. A total of 130 genes were annotated, including 85 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Comparison of cp genomes of four species from Onagraceae indicated that Onagraceae cp genomes had high nucleotide diversity. In addition, a few highly variable regions of these cp genomes were also detected. The phylogenetic tree showed that G. parviflora is closely related to Oenothera. Thus, the chloroplast genome of G. parviflora can provide valuable genetic information for species identification and phylogenetic analysis.